1998
DOI: 10.1542/peds.101.1.77
|View full text |Cite
|
Sign up to set email alerts
|

The Apgar Score and Its Components in the Preterm Infant

Abstract: Among the components of the Apgar score, respiratory effort, muscle tone, and reflex activity correlated well with one another; heart rate correlated less well; and color the least. Our data confirms the limited use of the Apgar score in preterm infants and demonstrates the different responses of the Apgar score's components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
91
0
3

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(102 citation statements)
references
References 16 publications
8
91
0
3
Order By: Relevance
“…Neonatal resuscitation among preterm infants improves with experience and education of provider institution [25][26][27]. Normal 5-minutes Apgar [28] (7.9 ± 1.2, Table 2) in the present study indicated overall success of neonatal resuscitative effort provided to study infants after birth. Mothers' tend to experience more severe psychological stress when an infant appears more critically ill [29,30].…”
Section: Discussionsupporting
confidence: 49%
“…Neonatal resuscitation among preterm infants improves with experience and education of provider institution [25][26][27]. Normal 5-minutes Apgar [28] (7.9 ± 1.2, Table 2) in the present study indicated overall success of neonatal resuscitative effort provided to study infants after birth. Mothers' tend to experience more severe psychological stress when an infant appears more critically ill [29,30].…”
Section: Discussionsupporting
confidence: 49%
“…Since this is a retrospective, single-center study, it also makes it difficult to generalize the results. This study was designed primarily to look at differences in overall Apgar scores, which has some limitations for use in extremely preterm neonates, 9 but is widely used nonetheless. Instead, an improvement in heart rate may have been a better indicator of response to resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…A 5-minute APGAR score of less than 7 was considered predictive of poor infant outcome. 9,10 The final outcome examined was infant death at less than a year of age.…”
Section: Methodsmentioning
confidence: 99%